Pre- and early in-hospital procedures in patients with acute coronary syndromes: first results of the “German chest pain unit registry” - Post, Felix; Giannitsis, Evangelos; Katus, Hugo; Senges, Jochen (Clinical research in cardiology, 2012)
BackgroundIn an attempt to improve the treatment of patients with acute coronary syndromes (ACS), a network of certified chest pain units (CPUs) has been recently established in Germany.MethodsData from patients admitted between December 2008 and September 2011 for ACS in 40 certified CPUs participating in the registry were prospectively collected.ResultsA total of 5,457 patients was admitted for ACS; 798 patients (14.6 %) were diagnosed with an ST-elevation myocardial infarction (STEMI), 2,244 (41.1 %) with a non-ST-elevation myocardial infarction (NSTEMI), and 2,415 (44.3 %) with unstable angina. The mean time to first medical contact was 2:08 h for STEMI patients. A pre-hospital ECG was available in 23.8 % of all ACS patients. Importantly, evidence of ST-segment elevation was present in 79.7 % of the STEMI patients already in this pre-hospital ECG. As many as 76.6 % of the patients, independently of their symptoms and final diagnosis, received an ECG within 10 min of reaching the CPU. 98.2 % of STEMI patients underwent invasive diagnostics, with an in-hospital delay as little as 31 (11-75) min.ConclusionThe establishment of a nation-wide network of certified CPUs optimizes the medical treatment of patients with ACS while providing an ideal infrastructure to evaluate and improve, both on a nation-wide and a single center scale, the adherence to guidelines. The median delay between symptom onset and first medical contact remains high. Although performed relatively rarely, a pre-hospital ECG facilitates earlier diagnosis of a STEMI in a large majority of patients. The introduction of CPUs minimizes in-hospital delays and exploits the benefit of invasive diagnostics and treatment.